Konsep Eskatologi Imam AL-Ghazali dan Relevansinya dengan Konstruksi Pemikiran Islam - Musthofa Bishri; Encung (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to examine the concept of eschatology according to Imam al-Ghazali, its stages, and its relevance in the construction of Islamic thought. The method used in this research is qualitative-descriptive with a literature study approach. Data were collected from various works of al-Ghazali, such as Ihya’ ‘Ulumuddin, as well as relevant classical and contemporary Islamic literature. The analysis was conducted using theological and philosophical approaches to gain a deep understanding of al-Ghazali’s ideas.The findings show that al-Ghazali divides eschatology into several main stages: death, life in the barzakh realm, resurrection, hisab (reckoning), sirat (the bridge), and the final journey of humans to either paradise or hell. Al-Ghazali employs sensory, imaginative, and rational approaches in explaining the concept of the pleasures of paradise and the torments of hell. His emphasis on divine justice and mercy serves as the fundamental basis of his eschatological conception. This study contributes to Islamic eschatology studies by highlighting the integration of theological, philosophical, and spiritual aspects in al-Ghazali’s thought. The findings demonstrate the relevance of al-Ghazali’s perspectives in understanding life after death and the significance of eschatology in the construction of Islamic thought.